2011
DOI: 10.1002/eat.20937
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine induced dopamine release increases anxiety in individuals recovered from anorexia nervosa

Abstract: Objective Genetic, pharmacologic, and physiological data suggest that individuals with anorexia nervosa (AN) have altered striatal dopamine (DA) function. Method We used an amphetamine challenge and positron emission tomography [11C]raclopride paradigm to explore DA striatal transmission in 10 recovered (REC) AN compared to 9 control women (CW). Results REC AN and CW were similar for baseline, post-amphetamine [11C]raclopride binding potential (BPND) and change (Δ) in BPND for all regions. In CW, ventral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 60 publications
(121 reference statements)
2
29
1
1
Order By: Relevance
“…Indeed, food ingestion may be experienced as anxiogenic for individuals with AN (Bailer et al, 2012). This may provide one mechanism through which individuals with AN experience self-starvation as a relief from this food associated anxiety, and indicates that negative reinforcement plays a big role in the maintenance of AN.…”
Section: The Role Of Positive and Negative Reinforcement In Compulsivitymentioning
confidence: 99%
“…Indeed, food ingestion may be experienced as anxiogenic for individuals with AN (Bailer et al, 2012). This may provide one mechanism through which individuals with AN experience self-starvation as a relief from this food associated anxiety, and indicates that negative reinforcement plays a big role in the maintenance of AN.…”
Section: The Role Of Positive and Negative Reinforcement In Compulsivitymentioning
confidence: 99%
“…(37) Importantly, rats characterized as risk aversive(39) showed greater D2 mRNA expression in the dorsal caudate, supporting human studies suggesting that DA signaling in executive cortical striatal circuitry is related to risk of adverse consequences or inhibitory control(40, 41) or anxiety. (42) A study(43) using PET [ 11 C]raclopride binding with amphetamine to assess endogenous DA production found that DA release in the precommissural dorsal caudate (preDCA) was associated with increased anxiety in REC AN. In contrast, controls showed euphoria associated with AVS DA release, consistent with many, but not all control responses to amphetamine.…”
Section: Da Function In An and Bnmentioning
confidence: 99%
“…This reduction of D2Rs is associated with suppressed metabolism in brain areas involved in self-control and increased metabolism in regions involved in sensory processing of palatability [185, 189]. Interestingly, a recent imaging study of patients recovered from anorexia nervosa indicates that their eating-induced dopamine release may produce anxiety instead of the typical pleasurable response [190]. …”
Section: Perturbations In Pathways That Regulate Behavior and Metabolmentioning
confidence: 99%